A new species and four new records of sedentary polychaetes from the Canadian High Arctic. (21st July 2016) - López, Eduardo; Olivier, Fredéric; Grant, Cindy; Archambault, Philippe
Abstract : During ArcticNet surveys aboard 'CCGS Amundsen' in 2011, several subtidal stations located in Canadian Archipelago were sampled in order to study the composition of their benthic communities. Among the abundant material sampled, several specimens of rare polychaete species were found. Examination of this material showed four species not previously recorded in the area, and a new species described herein. Descriptions of these specimens are given in this work. Ophelina brattegardi Kongsrud et al ., 2011 is characterized by a body composed of 27–28 chaetigers, by having the parapodia of the last four chaetigers shifted to the ventral side of the body, and by lacking branchiae in mid-body chaetigers. Macrochaeta polyonix Eliason, 1962 is unique within the genus in having several (instead of one or two) compound neurochaetae in anterior parapodia. Chaetozone acuta Banse & Hobson, 1968 is characterized by having spines from anterior third of the body and arranged in bundles composed of just a few chaetae. Chaetozone jubata Chambers & Woodham, 2003 can be distinguished from similar species by having very long capillary chaetae from chaetiger 2 or 3. Finally, Dialychone hervyae n. sp. is characterized by bearing four pairs of radioles with narrow flanges, by the bilobed tip of its first peristomial ring that projects beyond the collar, and by the paleate thoracic notochaetae bearing long mucros.